Hypnosis: Adjunct Therapy for Cancer Pain Management - Kravits, Kathy (Harborside Press, 2013)
Pain is a symptom associated with prolonged recovery from illness and procedures, decreased quality of life, and increased health-care costs. While there have been advances in the management of cancer pain, there is a need for therapeutic strategies that complement pharmaceutical management without significantly contributing to the side-effect profile of these agents. Hypnosis provides a safe and efficacious supplement to pharmaceutical management of cancer pain. One barrier to the regular use of hypnosis is health-care providers’ lack of current knowledge of the efficacy and safety of hypnosis. Advanced practitioners who are well-informed about hypnosis have an opportunity to increase the treatment options for patients who are suffering with cancer pain by suggesting to the health-care team that hypnosis be incorporated into the plan of care. Integration of hypnosis into the standard of care will benefit patients, caregivers, and survivors by reducing pain and the suffering associated with it.